CORRELATION ANALYSIS OF ONLINE LEARNING ASSIGNMENTS WITH STUDENT’S LEARNING INTEREST DURING THE COVID-19 PANDEMIC - Romadhon, Maria Haniffiah; Anshori, A.M.Miftah (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
Online learning is the use of internet as a media or support for the learning process which during the covid-19 pandemic, this media is very useful to replace normal learning carried out in the classroom. The main purpose of this study was to determine was there a correlation between the online assignment method and student learning interest in the Islamic Cultural History subject at MA Ma'arif NU Doplang during the covid-19 pandemic or not. The research method used in this study is a descriptive correlational method using a quantitative approach. The main data in this study are the results of observations, interviews, questionnaires, and documentation related to the correlation of the online assignment method with student interest in learning at Madrasah Aliyah Ma'arif NU Doplang second semester for the 2019/2020 academic year. Based on the results of data processing, it shows that there is a positive relationship between the use of the online assignment method and student’s learning interest in Islamic Cultural History subjects at Madrasah Aliyah Ma'arif NU Doplang with a rxy value of 0.886. This shows that there is a positive relationship between the use of the online assignment method and student interest in learning at Madrasah Aliyah Ma'arif NU Doplang.